Biocontrol efficacy of Trichoderma asperellum against fusarium wilt in tomato plants by induction of the host defense genes - Mahbuba Kaniz Hasna; Nipa Rani Paul; Mohammad Mahbubul Haque; Md. Shahidul Haque Bir; Md. Arshad Ali; Chong, Khim Phin (Springer Nature, 2025)
Fusarium wilt of tomato caused by Fusarium oxysporum f. sp. lycopersici causes large-scale loss in yield. In vivo and in vitro studies were conducted to evaluate the potential of Trichoderma asperellum for disease suppression. The present study investigated the efect of T. asperellum on the induced resistance in tomato plants through activating defense-related genes. In vitro test, 90% growth of F. oxysporum was reduced by T. asperellum after 6 days of confrontation. In vivo test, the AUDPC was 242.84 in the T. asperellum treated plant, but AUDPC was 351.34 in the T. asperellum and Fusarium treated plant. Microbial biopriming with T. asperellum resulted in enhanced expression of tomato defense-related genes. Only T. asperellum-treated plants expressed gene ratios for PAL3, PR10, PRS, CH4, and PR4 were 10, 170, 4, 45, and 50 respectively. In contrast, T. asperellum+F. oxysporum-treated plants expressed PR10, and PR4 gene ratios were 60 and 40 respectively. F. oxysporum-treated plants showed a PR10 gene expression ratio of 55. The qRT-PCR results showed that the induced systemic resistance (ISR) was primed while T. asperellum was challenged with F. oxysporum. Thus T. asperellum can be suggested as a potential biocontrol agent for fusarium wilt management.